Why Learning Arabic? (Maqasid Approach in Formulating Arabic Learning Curriculum) - Annafiri, Ahmad Zaki (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This study aims to carry out a Maqasid approach to learning Arabic. This study uses a qualitative approach with a descriptive analysis method. Researchers use the book Al Maqasid for Beginners by Jaser 'Audah as a primary source and studies of books, articles, journals, and related scientific works as a secondary source. Researchers will discuss three main aspects of learning Arabic: á¸aruriyyat, á¸¥ajiyyat, and tahsiniyyat aspects. The results of this study: 1) In the á¸aruriyyat aspect, the things that need to be considered are the meaning of the concepts of Al-Ilah, Ar-Rab, Ad-Din, Ar-Rasul, Al-Ibadah, and At-Taqwa, then proceed to the related understanding haá¸arah, thaqafah, umran, and tamaddun as part of Islamic civilization, 2) in the á¸¥ajiyyat aspect, two main points need to be considered, namely the sense of the moment and social media as a weapon. These two points result from â€˜hajahâ€™ or the need for students as objects of education in the context of current developments, 3) the tahsiniyyat aspect of the purpose of learning Arabic can be implemented in learning Arabic in the interest of getting benefits, both material and political benefits. By exploring and interpreting these three aspects of the maqasid perspective, students can understand their purpose for studying Arabic properly.ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ ØªÙ†ÙÙŠØ° Ù…Ù†Ù‡Ø¬ Ù…Ù‚Ø§ØµØ¯ Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. ØªØ³ØªØ®Ø¯Ù… Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù†ÙˆØ¹ÙŠ Ù…Ø¹ Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„ÙˆØµÙÙŠ. ÙŠØ³ØªØ®Ø¯Ù… Ø§Ù„Ø¨Ø§ØØ«ÙˆÙ† ÙƒØªØ§Ø¨ Ø§Ù„Ù…Ù‚Ø§ØµØ¯ Ù„Ù„Ù…Ø¨ØªØ¯Ø¦ÙŠÙ† Ù„Ø¬Ø§Ø³Ø± Ø¹ÙˆØ¯Ø© ÙƒÙ…ØµØ¯Ø± Ø£Ø³Ø§Ø³ÙŠ ÙˆØ¯Ø±Ø§Ø³Ø§Øª Ø§Ù„ÙƒØªØ¨ ÙˆØ§Ù„Ù…Ù‚Ø§Ù„Ø§Øª ÙˆØ§Ù„Ù…Ø¬Ù„Ø§Øª ÙˆØ§Ù„Ø£Ø¹Ù…Ø§Ù„ Ø§Ù„Ø¹Ù„Ù…ÙŠØ© Ø°Ø§Øª Ø§Ù„ØµÙ„Ø© ÙƒÙ…ØµØ¯Ø± Ø«Ø§Ù†ÙˆÙŠ. Ø³ÙŠÙ†Ø§Ù‚Ø´ Ø§Ù„Ø¨Ø§ØØ«ÙˆÙ† Ø«Ù„Ø§Ø«Ø© Ø¬ÙˆØ§Ù†Ø¨ Ø±Ø¦ÙŠØ³ÙŠØ© Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©: Ø¬ÙˆØ§Ù†Ø¨ Ø§Ù„ØµØ±Ø±ÙŠØ§Øª ÙˆØ§Ù„ØØ¬ÙŠØ§Øª ÙˆØ§Ù„ØªØØ³ÙŠÙ†ÙŠØ§Øª. ÙˆÙ†ØªØ§Ø¦Ø¬ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø©: 1) Ù…Ù† Ù†Ø§ØÙŠØ© Ø§Ù„Ø³Ø±ÙŠØ§Øª ØŒ ÙØ¥Ù† Ø§Ù„Ø£Ù…ÙˆØ± Ø§Ù„ØªÙŠ ÙŠØ¬Ø¨ Ù…Ø±Ø§Ø¹Ø§ØªÙ‡Ø§ Ù‡ÙŠ Ù…Ø¹Ù†Ù‰ Ù…ÙØ§Ù‡ÙŠÙ… Ø§Ù„Ø¥Ù„Ù‡ ÙˆØ§Ù„Ø±Ø¨ ÙˆØ§Ù„Ø¯ÙŠÙ† ÙˆØ§Ù„Ø±Ø³ÙˆÙ„ ÙˆØ§Ù„Ø¹Ø¨Ø§Ø¯Ø© ÙˆØ§Ù„Ø¹Ø¨Ø§Ø¯Ø©. Ø§Ù„ØªÙ‚ÙˆÙ‰ ØŒ Ø«Ù… Ø§Ù†ØªÙ‚Ù„ Ø¥Ù„Ù‰ Ø§Ù„ÙÙ‡Ù… Ø°ÙŠ Ø§Ù„ØµÙ„Ø© Ø§Ù„ØØ§Ø±Ø© ØŒ ÙˆØ§Ù„Ø«Ù‚Ø§ÙØ© ØŒ ÙˆØ§Ù„Ø¹Ù…Ø±Ø§Ù† ØŒ ÙˆØ§Ù„ØªÙ…Ø¯Ù† ÙƒØ¬Ø²Ø¡ Ù…Ù† Ø§Ù„ØØ¶Ø§Ø±Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©ØŒ 2) ÙÙŠ Ø§Ù„Ø¬Ø§Ù†Ø¨ Ø§Ù„ØØ¬ÙŠØ§Øª ØŒ Ù‡Ù†Ø§Ùƒ Ù†Ù‚Ø·ØªØ§Ù† Ø£Ø³Ø§Ø³ÙŠØªØ§Ù† ÙŠØ¬Ø¨ Ø£Ø®Ø°Ù‡Ù…Ø§ ÙÙŠ Ø§Ù„Ø§Ø¹ØªØ¨Ø§Ø± ØŒ ÙˆÙ‡Ù…Ø§ Ø§Ù„Ø´Ø¹ÙˆØ± Ø¨Ø§Ù„Ù„ØØ¸Ø© ÙˆÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªÙˆØ§ØµÙ„ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ ÙƒØ³Ù„Ø§Ø. Ù‡Ø§ØªØ§Ù† Ø§Ù„Ù†Ù‚Ø·ØªØ§Ù† Ù†Ø§ØªØ¬ØªØ§Ù† Ø¹Ù†